Al-Ghazali's Ethics in Supporting Character Education The Perspective of the Manggarai Community through Uwa Haeng Wulang Langkas Haeng Ntala - Yulianus Gunawan Mamput (Fakultas Teologi, Universitas Sanata Dharma, 2024)
This article discusses the correlation between the local wisdom of the Manggarai community expressed in the proverb